Study of Asynchronous Analog-To-Digital Converter In Cad Graphics: Design and Simulation of a High-Speed Low Power Asynchronous ADC in CAD Graphics (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This paper contains the asynchronousADC design specification which has high speed and low power. Asynchronous ADC consists of 3 blocksof units composer OPAMP, Digital Logic and Switch Capacitor. Needs high-speedADC is needed to convert analog signals to digital which is applied to amultimedia device, especially for video signal applications. Low power consumptionis useful for efficient power use. The method used in the design is anexperiment with simulation CAD software mentor graphics technology withtechnology CMOS of AMS (Austria Micro Systems) 0.35 μm. Stage design is theA-ADC circuit design with simulation results. The end result is to obtain adesign prototype A-3-bits ADC, power consumption